EXPLORING THE MICROPLASTICS DISTRIBUTION IN THE BOTTOM SEDIMENTS OF THE WESTERN BLACK SEA - IEMELIANOV, Volodymyr; NASIEDKIN, Yevhen; KUKOVSKA, Tamara; KOSHLIAKOVA, Tetiana; FEDORONCHUK, Natalia; SHURAIEV, Іhor; YUKHYMCHUK, Volodymyr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The spread and accumulation of plastic waste in the environment is now a recognized global problem. The development of an effective strategy for managing plastic waste and minimizing its impact on the marine environment is not possible without conducting field studies in bottom sediments. Determination of their content in the upper layer of precipitation and study of qualitative and quantitative characteristics will allow to outline the patterns of their entry into the water area, distribution and accumulation, risks of impact on marine organisms.Methods. Visual determination of microplastic particles was carried out under the monocular of SIGETA MB-12 LCD optical microscope. An alternative method of identification, the hot needle test, was also used to determine plastic under the microscope. Raman spectroscopy was used to perform structural identification. Laboratory studies were performed using a single-stage MDR-23 spectrometer equipped with a cooled CCD detector and a Micromed microscope.Results. The analysis of each sample and subsequent generalization showed the presence of plastic particles at all points of the sampling area, in different quantities and composition. The results of our studies confirm that microplastic particles in the surface sediments are quite abundant throughout the entire research area, and they are represented by different types everywhere, with fibers dominating in terms of morphological characteristics and polyethylene and polypropylene in terms of chemical types. There is no stable dependence of redistribution of microplastics of different densities on distance from the shore. The only thing that can be confirmed is uneven lateral distribution within the shelf zone, which is quite possibly related to the impact of the anthropogenic plane load on the surface bottom sediments.Conclusions. Studies have shown that microplastic particles in the surface sediments are quite abundant throughout the survey area, and they are represented by different types everywhere, with fibers dominating in terms of morphological characteristics. As for the distribution of microplastics in surface sediments depending on natural conditions, we can document the fact that the amount of polymers, in terms of dry weight of soil matrix samples, increases in the direction of the mainland slope. An important result of the work was the identification of a number of topical issues, shortcomings and uncertainties in laboratory research methods, sample preparation and identifying microplastics, which should be addressed in the future.
Keywords: microplastics; bottom sediments; research methods; ecology; spectroscopy; visual examinations